Combined Radiological Intervention and Surgical Excision of a Periorbital Arteriovenous Fistula. (June 2013) - Tan, Bernard; Rootman, Jack; Seah, Lay Leng
ABSTRACT Objective: To describe a case of periorbital arteriovenous fistula (AVF) treated with a combined approach of endovascular intervention and surgical excision. Case report: A 21-year-old lady presented with a vascular lump followed blunt trauma above the left medial brow area. Computed Tomography Angiogram (CTA) and Angiography of the internal and external carotid arteries showed presence of an AVF with main feeder vessel from a hypoplastic left ophthalmic artery. Pre-operative radiological embolization was performed but the patient defaulted planned surgery. She returned 4 months later complaining of pain and increased swelling of the lesion. Repeat CTA demonstrated residual shunt located below the supra-orbital rim medially supplied by the left supratrochlear artery. Excision was later performed without repeat embolization and was uncomplicated. Histological reported chronic inflammation with granulomatous foreign body giant cell reaction confirming pre-operative diagnosis of tissue reaction to glue cast. Conclusion: Treatments of Orbital AVFs are challenging and require multidisciplinary team management involving interventional radiologists and orbital surgeons. A foreign body reaction can develop followed embolization with tissue glue alone. Prompt surgical excision is therefore recommended to minimize post operation morbidity.